YOUTH POLICY AND MEDIA: THE RISING GENERATION IN THE INFORMATION SOCIETY (Sciental Journal of Education Humanities and Social Sciences, 2026)
This article is devoted to studying the role and significance of mass media in shaping the political culture and political behavior of youth within the context of an information society. The article analyzes the interaction between youth and media, the mechanisms of forming political decisions and values through information flows, as well as the impact of media tools on social and political consciousness. At the same time, the article provides recommendations for increasing the political activity of young people in an information society and guiding them toward responsible citizenship.